Water as Human Right: Impact of Thai Binh 1 Thermal Plant Project on Domestic Water Supply of Riverine People in Chi Thien Village, Vietnam - Thuy Nga, Dinh Thi (Kathmandu School of Law Review, 2018)
The research studies on the typical context of Chi Thien village, an area having new-operated coal-power plant as the development project in the northern part of Vietnam. As the focus of the research, domestic water supply is studied. Conventionally, villagers harvest rainwater into big reservoirs that later on were demolished for house renovation after the agricultural compensation for the coal plant construction. Since the establishment of the Thai Binh 1 Thermal plant, locals are recommended not to drink raining water because of potential negative impacts of coal ash on human health. Findings of the research indicate that local households have been provided with tap water service since 2014 by the Chieu River water plant of the local authority. However, doubts on the low tap water quality and its unstable frequency, rainwater returns to be the preferable choice for their domestic water supply. There is a regular check on water affirmed by the engineer from Chieu River plant. Nevertheless, for confidentiality, it was not allowed to publish regardless of the request to have evidence on qualified tap water. This is considered as the violation of the right to information and the participation in environmental decision making of the villagers. For certain disadvantages of water situation, local people have adaptation by buying reverse osmosis(RO)water filters(wealthier family only)and need to pay for water consumption expense with the low quality received. Study on domestic water is a study on human well-being, human rights and state obligation to ensure the water sanitation, the accessibility, and affordability to people. The role of the Vietnamese government is analyzed in addressing these potential impacts caused by the coal plant project towards an adequate standard of living and the highest attainable standard of health in Chi Thien. The thesis is social research using qualitative research methodology of in-depth interviews and referral samples to approach the topic and elicit reliable information, particularly on opinions and hands-on experiences of villagers.DOI: https://doi.org/10.46985/jms.v6i2.204